Peningkatan Kompetensi Perangkat Desa dalam Pembuatan Materi Publikasi Berbantuan Artificial Intelligence - Gustin Setyaningsih; Muhamad Awiet Wiedanto Prasetyo (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
The limited artificial intelligence literacy of village officials restricts the use of AI in producing public information materials and lacked an understanding of structured prompt development. This community service activity aimed to improve their understanding and ability to use AI for producing activity news, social media captions, announcements, public service information, and poster concepts. The activity was conducted at Pekuncen Village Hall, Kroya District, Cilacap Regency, and involved nine village officials. A participatory approach was implemented through a pretest, material presentation, demonstration, discussion, guided practice, and posttest. The evaluation instrument consisted of 20 Likert-scale statements covering basic AI knowledge, AI benefits and limitations, prompt development, the use of AI for publication, and data ethics and security. The results showed that the participants’ average score increased from 50.89 in the pretest to 83.44 in the posttest, representing an improvement of 63.97%. The greatest improvement occurred in prompt development skills, with the average score increasing from 2.26 to 4.02. Participants also became more capable of verifying facts, editing AI-generated outputs, and avoiding the use of personal data in public AI applications. These findings indicate that practice-based training can improve village officials perceived understanding and ability to use AI critically, safely, and responsibly.